Hematological and blood chemistry values in captive Japanese macaques (Macaca fuscata fuscata). Issue 6 (16th August 2019) - Miyabe‐Nishiwaki, Takako; MacIntosh, Andrew J. J.; Kaneko, Akihisa; Morimoto, Mayumi; Suzuki, Juri; Akari, Hirofumi; Okamoto, Munehiro
Abstract: Background: Biological information about captive Japanese macaques, including hematology and blood chemistry, is still lacking despite the fact that ethological and ecological data have accumulated during decades of field research. Methods: Hematological (511 examinations of 280 Japanese macaques) and blood chemistry data (between 33 and 284 examinations from between 29 and 257 individual macaques) in clinically healthy, simian retrovirus‐free Japanese macaques tested between 2009 and 2013 were reviewed. Results and Conclusions: Specific hematological and blood chemistry data for Japanese macaques without clinical signs of disease were provided in this study. Averages presented can be used as hematological parameters for Japanese macaques. Some differences between Japanese macaques and other closely related macaque species were found. Some parameters varied according to macaque age and sex, as well as regional origin. The data in this study will provide useful clinical indices for Japanese macaques in captive and similar conditions.